Research Progress and the Development Trend of the Utilization of Crop Straw Biomass Resources in China - Yang, Wei; Li, Xiaohua; Zhang, Yutao (Frontiers in Chemistry, 2022)
The utilization of crop straw biomass resource is highly emphasized by governments as well as the academia in recent decades. Based on the core databases of literature in China National Knowledge Infrastructure (CNKI) academic journals, CiteSpace software is used to analyze and process the hot spots, and this paper proposed the primary coverage and evolutionary trends of research on the utilization of crop straw resource. The thesis proposes the research development trend of improving the institutional mechanism of the utilization of crop straw resource, strengthening technology research and development, exploring the economic model of green cycle agriculture, accelerating the construction of industrial system and designing new paths of resource utilization in multiple ways, which helps to estimate the development trend of the utilization of crop straw resource and provides inspiration and direction for future researches and practices.